MOBILE LEARNING IN PEDAGOGY - Akhmadjonova Mutabarkhon; Dadajonova Feruzakhon; Gaforov Iqboljon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article is about new distant learning which is by least modern technology. Term of mobile learning was not popular until pandemic. After that this kind of learning resource has come into our country. Most people as well as young children use the internet in social life every day and we can not imagine our life without it because any information or news is taken by social media. So nowadays way of mobile learning is more comfortable for instance, it can help to time consuming, convenient environment and ect. Overall, the article emphasizes mobile learning is one of the best way both students and other learners. It is an innovative approach that leverages the convenience and ubiquity of mobile devices to enhance pedagogy.